Seismic performance of single-storey light timber-framed buildings braced by gypsum plasterboards considering rigidity of ceiling diaphragms. (July 2022) - Ma, Zhong; Li, Minghao; Liu, Angela; Wang, Jingfeng; Zhou, Lina; Dong, Wenchen
Abstract: Light timber framed (LTF) structures provide a cost-effective and structurally efficient solution for low-rise residential buildings. This paper studies seismic performance of single-storey LTF buildings sheathed by gypsum-plasterboards (GPBs) that are a typical lining product in New Zealand houses. Compared with wood-based structural panels, GPBs tend to be more susceptible to damage when they are used in bracing walls to resist earthquake loads. This study aims to provide insights on how the bracing wall irregularity allowed by the current New Zealand standard NZS 3604 and the in-plane rigidity of ceiling diaphragms affect the overall seismic performance of these GPB-braced LTF buildings. Nonlinear time-history analyses were conducted on a series of single-storey baseline buildings with different levels of bracing wall irregularities and ceiling diaphragm rigidity. The results showed significant torsional effect caused by the eccentric bracing wall layout with semi-rigid/rigid ceiling diaphragms. On average, bracing wall drift demand caused by the extreme bracing wall irregularities was three times of that in the regular bracing wall layout under the rigid diaphragm assumption. This finding agreed well with the house survey after the 2011 Canterbury Earthquake in which significantly more damage was observed in the houses with irregular bracing wall layouts and relatively rigid diaphragms. Therefore, it is recommended to limit the level of bracing wall eccentricity and ensure the sufficiently rigid diaphragms to avoid excessive damage in these LTF buildings in future events.